A Flexible Multifunctional Tactile Sensor Using Interlocked ZnO Nanorod Arrays for Artificial Electronic Skin. (2016) - Suen, Min-Sheng; Lin, Yi-Cheng; Chen, Rongshun
Abstract: This study presents a novel multifunctional tactile sensor to mimetic the human skin with high sensitive, flexible, and temperature measurable performances. The substrate is flexible due to the material property of the Polydimethylsiloxane (PDMS). The top electrode and bottom electrode layers are interlocked by the zinc oxide (ZnO) nanorods, which is vertically growing on the top of PDMS, providing high sensitivity for the measurement of the contact force and environment temperature. In this work, we successfully fabricated the tactile sensor array with multiple functions mentioned above by the experiments, which is expected to be employed in the artificial electronic skin (e-skin). In the future, the proposed tactile sensor can be utilized in the wearable device, flexible interface, and bionic robot skin in the industry.